Motivasi dan Efikasi Diri: Peran Manajemen Waktu dalam Meningkatkan Kinerja Perawat (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the influence of motivation and self-efficacy on nurse performance, with time management as a moderating variable. The research method uses a quantitative approach with a survey technique, where data is obtained from nurses working in nursing homes in Japan. The research method uses a quantitative approach with a survey technique, where data is obtained from nurses working in nursing homes in Japan. The results of the analysis show that motivation and self-efficacy have a significant positive effect on nurse performance. In addition, time management moderates the relationship between motivation and performance, where nurses with good time management skills show greater performance improvement. However, the moderating effect of time management on the relationship between self-efficacy and nurse performance is not significant. These findings have practical implications for nursing home management to develop programs to improve motivation and self-efficacy, as well as time management training to improve nurse productivity. This study is expected to contribute to the literature on human resource management in the health sector, especially in the context of elderly care in Japan.  Keywords: Motivation, Self-Efficacy, Nurse Performance, Time Management, Japan